The Na+/K+-ATPase: A potential therapeutic target in cardiometabolic diseases - Obradovic, Milan; Sudar-Milovanovic, Emina; Gluvic, Zoran; Banjac, Katarina; Rizzo, Manfredi; Isenovic, Esma R. (Frontiers in Endocrinology, 2023)
Cardiometabolic diseases (CMD) are a direct consequence of modern living and contribute to the development of multisystem diseases such as cardiovascular diseases and diabetes mellitus (DM). CMD has reached epidemic proportions worldwide. A sodium pump (Na+/K+-ATPase) is found in the membrane of most eukaryotic cells and is in control of many essential cellular functions directly or indirectly. This ion transporter and its isoforms are important in the pathogenesis of some pathological processes, including CMD. The structure and function of Na+/K+-ATPase, its expression and distribution in tissues, and its interactions with known ligands such as cardiotonic steroids and other suspected endogenous regulators are discussed in this review. In addition, we reviewed recent literature data related to the involvement of Na+/K+-ATPase activity dysfunction in CMD, focusing on the Na+/K+-ATPase as a potential therapeutic target in CMD.